Effects of Low-Carbohydrate Diet and Exercise Training on Gut Microbiota - Sun, Shengyan; Lei, On Kei; Nie, Jinlei; Shi, Qingde; Xu, Yuming; Kong, Zhaowei (Frontiers in Nutrition, 2022)
Objective: This study aimed to evaluate the effects of low-carbohydrate diet (LC) and incorporated high-intensity interval training (HIIT) or moderate-intensity continuous training (MICT) on gut microbiota, and the associations between changes in gut microbiota and cardiometabolic-related profiles. Methods: Fifty overweight Chinese females (age 22.2 ± 3.3 years, body mass index 25.1 ± 3.1 kg·m-2) were randomized to the groups of LC control (LC-CON), LC and HIIT (LC-HIIT, 10 repetitions of 6-s sprints and 9-s rest), and LC and MICT group (LC-MICT, cycling at 50-60% V̇O2peak for 30 min). The HIIT and MICT experienced 20 training sessions over 4 weeks. Results: The 4-week LC intervention with/without additional training, failed to change the Shannon, Chao 1 and Simpson indexes (p>0.05), LC-CON increased Phascolarctobacterium genus and LC-HIIT reduced Bifidobacterium genus after intervention (p<0.05). Groups with extra exercise trianing increased SCFA-producing Blautia genus (p<0.05) and reduced type 2 diabetes-related genus Alistipes (p<0.05) compared to LC-CON. Sutterella (r = -0.335) and Enterobacter (r = 0.334) were associated with changes in body composition (p<0.05). Changes in Ruminococcus, Eubacterium, and Roseburia genera were positively associated with blood pressure (BP) changes (r = 0.392–0.445, p<0.05), whereas the changes in Bacteroides, Faecalibacterium and Parabacteroides genera were negatively associated with BP changes (r = -0.567– -0.362, p<0.05). Conclusion: LC intervention did not change the α-diversity, and overall structure of gut microbiota. Combining LC with exercise training may have additional benefits on gut physiology. Specific microbial genera were associated with LC- and exercise-induced regulation of cardiometabolic health.